Diseño y fabricación de un prototipo de bomba diafragma de doble efecto, accionada por rueda hidráulica de ocho palas. - Aguirre Buñay, Stalin David (2023)
The purpose of this thesis was to design and manufacture a prototype diaphragm pump that was coupled to an eight-bladed hydraulic wheel to put a pumping system into operation. This system benefits both the students and the community near the Santa Lucía sector. For the design of the diaphragm pump, a hydraulic wheel located in the Illuchi River was considered, which provides 10 revolutions per minute and a torque of 75.6 Nm, and which activates the connecting rod-crank mechanism. The hydraulic installation, made up of PVC pipes, begins in the suction part, where a 1" foot valve is connected, and continues in the discharge part, where a ½" check valve has been installed. In addition, a hydropneumatic tank was incorporated to stabilize the flow, since, being a volumetric pump, the flow presented fluctuations. For the design and analysis of each component, Autodesk Inventor software (version 2023) was used, obtaining a safety factor of no less than 1.4 and a maximum displacement of 0.06 mm. In addition, the tests carried out demonstrated optimal operation of the pumping system, obtaining the following results: a flow rate of 2.16 liters per minute and an average pressure of 117.37 kPa at a height of twelve meters. Since the river pump uses hydraulic energy, the approach of the thesis presented does not generate environmental impact. The cost to manufacture the system was 610 USD, and this investment is expected to be recovered over time due to its long durability and low maintenance cost.